The Phenomenon Of Fomo Among Teenagers And Its Educational Solution - Dyah Nawangsari; Aminullah Elhady (AIUA Journal of Islamic Education, 2019)
The intensity of the use of gadgets among teenagers has implications for the emergence of Fomo (Fear of Missing Out). They feel less confident when left behind in accessing information or contents on the gadgets. The results of a study of 571 parents who have children under 16 years of age, prove that a quarter of responders said their children felt 'missing' without technology. More than a quarter of responders also said they would spend more money on gadgets allocation than the previous year. This study describes: (1) What are the forms of Fomo among teenagers; (2) How does Fomo occur in teenagers; and (3) How educational solutions to overcome them. This study uses a combination of quantitative and qualitative approaches, resulting the following conclusions: (1) Some irregularities in the use of gadgets include: addiction to games, romantic show sites that lead to pornography and sites of violence show. (2) Fomo affects many teenagers for several reasons, including the desire to be accepted in their community, efforts to build self-confidence, and the search for identity. (3) Educational solutions in the context of overcoming them involve parents, schools, government, and the power of civil society.